2006
DOI: 10.1111/j.1525-1438.2006.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of galectin-1 during the progression of cervical neoplasia

Abstract: Galectin-1, a member of the beta-galactoside-binding family, is widely expressed in epithelial and immune cells. It is involved in several normal and pathologic processes, such as cancer progression, metastasis, and immunobiology. Galectin-1 was found to be overexpressed in various cancer cells and the corresponding benign tissue. Therefore, it has been described as a marker for tumor progression in some malignancies. In the current study, the expression of galectin-1 was examined in 80 formalin-fixed, paraffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
4
21
0
1
Order By: Relevance
“…For cervical cancer, different studies have linked the galectins expression to host-parasite interaction [17], neoplastic transformation [18][19][20], sensitivity to concurrent chemoradiotherapy [21,22], tumorigenesis [23,24], and cell growth [25]. However, little is known about the role of Gal-1 in invasive cervical cancer, especially in terms of tumor proliferation, invasion, or metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…For cervical cancer, different studies have linked the galectins expression to host-parasite interaction [17], neoplastic transformation [18][19][20], sensitivity to concurrent chemoradiotherapy [21,22], tumorigenesis [23,24], and cell growth [25]. However, little is known about the role of Gal-1 in invasive cervical cancer, especially in terms of tumor proliferation, invasion, or metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In squamous cervical cancer patients who received radiation therapy, a recent study reported that expression of galectin-1 by the tumor was an independent predictor for local recurrence and poor survival [27]. Expression of galectin-1 in the stroma of cervical cancer has also been correlated with higher histopathological grade [28] and lymph node metastasis [29]. Information about galectin-3 and galectin-9 expression in cervical cancer is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it exists intracellularly and interacts with cytoplasmic and nuclear proteins to regulate cell transformation (14) or pre-mRNA splicing (15). Immunohistochemical staining of Gal-1 in clinical cancer samples reveals that its expression is positively associated with the malignant progression of many tumor types, including glioma (16), prostate (17), colon (18), breast (19), cervical (20), and oral squamous (21) cells. The expression of Gal-1 in carcinoma-associated stromal cells was significantly correlated with breast tumor invasiveness and lymph node metastasis (19).…”
Section: Introductionmentioning
confidence: 99%